The Impact of predation on the abundance of steppe runners, Eremias arguta deserti (Gmelin, 1789), in semi-deserts of the southeastern part of the Lower Volga region - S.S. Mishustin; G.V. Polynova (Учёные записки Казанского университета: Серия Естественные науки)
The tail autotomy in the population of steppe runners (Eremias arguta deserti (Gmelin, 1789)) living in semi-deserts of the southeastern part of the Lower Volga region was studied. The proportion of lizards with the signs of tail autotomy was used as an indicator of predation pressure. It was found that the number of lizard individuals with autotomized (regenerated) tails increased throughout the research period (2017–2019). The correlation between the total abundance of lizards and the number of individuals with tail autotomy exhibits a direct and statistically insignificant dependence. The data obtained suggest that predators are low abundant, both in the study area and in the surrounding territories, and, thus, they have no considerable influence on the size of the population of lizards. No autotomy as a result of intra- and interspecific contacts was recorded. In the spring field seasons, the lizard individuals with autotomized (regenerated) tails were mainly mature males and females. In the autumn periods, they were exclusively underyearlings. In the population under consideration, lizards with the signs of tail autotomy were more frequent among the migrating individuals. There were no quantitative differences in the presence of tail autotomy between males and females.